Smad signalling in the ovary - Mottershead David G; Ritvos Olli; Jeffery Luke A; Kaivo-oja Noora (BMC, 2006)
Abstract It has now been a decade since the first discovery of the intracellular Smad proteins, the downstream signalling molecules of one of the most important growth factor families in the animal kingdom, the transforming growth factor beta (TGF-beta) superfamily. In the ovary, several TGF-beta superfamily members are expressed by the oocyte, granulosa and thecal cells at different stages of folliculogenesis, and they signal mainly through two different Smad pathways in an autocrine/paracrine manner. Defects in the upstream signalling cascade molecules, the ligands and receptors, are known to have adverse effects on ovarian organogenesis and folliculogenesis, but the role of the individual Smad proteins in the proper function of the ovary is just beginning to be understood for example through the use of Smad knockout models. Although most of the different Smad knockouts are embryonic lethal, it is known, however, that in Smad1 and Smad5 knockout mice primordial germ cell development is impaired and that Smad3 deficient mice harbouring a deletion in exon 8 exhibit impaired folliculogenesis and reduced fertility. In this minireview we discuss the role of Smad structure and function in the ovarian context.